SENI TARLING DAN PERKEMBANGANNYA DI CIREBON - Hidayatullah, Riyan (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2015)
The varieties of tarling music which keep changing and developing nowadays have brought two main concerns in our society: lack of identity function and music distortion. These issues may affect the loss of the originality of tarling music itself. This study aimed at knowing the development of tarling Cirebon and the change of tarling music at present day. The method used in this study was descriptive qualitative. The data regarding the art and tarling music were collected through library research and interview. Generally, tarling music is divided into two types: classical tarling music and modern Cirebon tarling music. Tarling music is the combination of different music genres like pop and dangdut. The collection of ideas of a certain community and that of the consolidated thoughts have become the sources of the tarling music development.Keywords: classical tarling, modern tarling, Cirebon